(untitled) (SAARC Journal of Agriculture, 2017)
Chilli price fluctuates more in every year in Bangladesh. Therefore, this crop is faced with the highest risk and uncertainty. Due to that, prediction is not possible on production correctly. The study was conducted to aim at the determination of fluctuation, and production-price relationship of chilli in Bangladesh. The experiment was carried out by using chilli area, production and prices data from Bangladesh Bureau of Statistics (1985-2014). Data were analyzed using simplest method for fluctuation, and the Koyck model of distributed lag models. The study showed that the extent of annual price fluctuation of chilli was identified which was between -55 to 111 per cent. Ten several causes were identified which have been the reason of unstable price of chilli. Government price control, improvement of production technology and other identified measures are urgently needed for preventing price fluctuation. According to the results, chilli production in Bangladesh has been influenced by the lag value of average price formed in the market. The most striking result of the study is that the time required for the changes in the chilli prices in Bangladesh to have an effect on chilli production is 6.09 years. The value of coefficient indicated that the changes in lag values of the prices had a positive influence on production, this influence was getting smaller. To reduce the risk and uncertainty of the price of chilli which caused fluctuation more, sustainable chilli farming and establishment of an efficient marketing organization is necessity. SAARC J. Agri., 15(1): 85-98 (2017)